Docosahexaenoic acid impacts macrophage phenotype subsets and phagolysosomal membrane permeability with particle exposure. Issue 4 (16th February 2021) - Fletcher, Paige; Hamilton, Raymond F.; Rhoderick, Joseph F.; Pestka, James J.; Holian, Andrij
ABSTRACT: Inhalation of particles results in pulmonary inflammation; however, treatments are currently lacking. Docosahexaenoic acid (DHA) is an omega-3 polyunsaturated fatty acid shown to exhibit anti-inflammatory capabilities. The impact of DHA on particle-induced inflammation is unclear; therefore, the aim of this study was to examine the hypothesis that DHA downregulates macrophage inflammatory responses by altering phagolysosomal membrane permeability (LMP) and shifting macrophage phenotype. Isolated Balb/c alveolar macrophages (AM) were polarized into M1, M2a, M2b, or M2c phenotypes in vitro, treated with DHA, and exposed to a multi-walled carbon nanotube (MWNCT) or crystalline silica (SiO2 ). Results showed minimal cytotoxicity, robust effects for silica particle uptake, and LMP differences between phenotypes. Docosahexaenoic acid prevented these effects to the greatest extent in M2c phenotype. To determine if DHA affected inflammation similarly in vivo, Balb/c mice were placed on a control or 1% DHA diet for 3 weeks, instilled with the same particles, and assessed 24 hr following instillation. Data demonstrated that in contrast to in vitro findings, DHA increased pulmonary inflammation and LMP. These results suggest that pulmonary responses in vivo may not necessarily be predicted from single-cell responses in vitro .